'Going under-employed': Industrial and regional effects, specialization and part-time work across recession-hit Southern European Union regions. (July 2018) - Gialis, Stelios; Gourzis, Kostas; Underthun, Anders
The paper explores the regional dimensions of under-employment by analysing the uneven dispersion of part-time jobs in Greece. It understands under-employment as an integral dimension of contemporary flexible labour trends, triggered by devaluation and expanding amid crisis, although in diverse geographical and sectoral terms. It follows a methodology that comparatively analyses statistical data, relevant secondary sources and previous case studies, before moving to a theoretical contextualization of the findings. Based on this framework, NUTS-II level total employment and part-time work data are analysed through location quotients, and a new embellishment of shift-share analysis is implemented for 2005–2008 and 2009–2012 across nine sectors. The findings reveal four distinct, although porous, patterns of under-employment that are distinguished according to different regional productive specializations and the impact of structural or regional effects. The reasons why some regional economies, such as the tourist ones, were more resistant to employment losses, and at the same time the most keen on expanding part-time work, are scrutinized. Concluding, three deeper causal mechanisms, namely productive-technological, organizational and institutional, that determine the under-employment patterns revealed, are discussed and contrasted to relevant literature findings.